On the Convergence of Solutions of Certain Third-Order Differential Equations - Ercan Tunç (Discrete Dynamics in Nature and Society, 2009)
We establish sufficient conditions for the convergence of solutions of a certain third-order nonlinear differential equations. By constructing a Lyapunov function as the basic tool, some results which exist in the relevant literature are generalized.